The Construction of Green Finance Strategies in Promoting Sustainable Investment Transformation: A Qualitative Study of Financial Institutions in Indonesia - Hariany Idris (Golden Ratio of Finance Management, 2026)
This study aims to analyze the construction of green finance strategies in promoting the transformation of sustainable investment within financial institutions in Indonesia. Specifically, it explores the factors influencing the adoption of green finance, the challenges encountered in its implementation, and the strategic opportunities for integrating sustainability principles into the national financial system. This research employs a qualitative approach using a systematic literature review method. Data were collected through an in-depth analysis of 47 peer-reviewed articles, regulatory policy documents, and sustainability reports from financial institutions published between 2019 and 2025. Thematic analysis was used to identify patterns, trends, and key findings related to green finance strategies. The results indicate that the development of green finance strategies in Indonesia is influenced by five main factors: a regulatory framework strengthened by the Financial Services Authority (OJK), internal environmental awareness, top management support, financial technology innovation, and external market pressure. The findings also reveal that the integration of Environmental, Social, and Governance (ESG) principles has a positive impact on financial stability and institutional reputation. Furthermore, this study finds that the success of sustainable investment transformation requires a holistic approach involving institutional capacity building, multi-stakeholder collaboration, and the development of innovative green financial products. However, several major challenges remain, including gaps in green financial literacy, inadequate standardization of ESG indicators, and the national economy’s continued dependence on fossil fuels. This study contributes to the literature by providing a comprehensive understanding of green finance strategy construction and its role in strengthening sustainable finance practices in Indonesia.